UJI PROGNOSTIK SKOR MOTORIK FREKUENSI NAFAS DAN MEMBUKA MATA M N M SKOR UNTUK MEMPREDIKSI KELUARAN DALAM TIGA HARI PADA PASIEN DEWASA TRAUMA KAPITIS SEDANGBERAT - Andrie Gunawan*, Lyna Soertidewi **, Eka Musridharta**, Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION ATTEMPT TO PREDICT PROGNOSIS AFTER CRANIOCEREBRAL INJURY IS VERY IMPORTANT AN ACCURATE INITIAL ASSESSMENT BY MEDICAL PERSONNEL ESPECIALLY ATTENDING PHYSICIAN IS NEEDED TO MAKE A RIGHT MANAGEMENT AND TO PREDICT OUTCOME INITIAL ASSESSMENT WITH SCORING TOOL IS A SIMPLEST METHOD TO ANSWER FAMILY QUESTION ESPECIALLY IN MEDICOLEGAL AND ADMINISTRATIVE ASPECTS